Insect Species Diversity in Oil Palm Plantation Area Wonosari Sub-District Boalemo District - Mursali, Intan Zulfatadila; Lamangantjo, Chairunnisah J.; Baderan, Dewi Wahyuni K.; Hamidun, Marini Susanti; Zakaria, Zuliyanto (Jurnal Biologi Tropis, 2025)
Each habitat has a drastically varied species composition as a result of oil palm plantations filtering out natural forest wildlife, leaving only a limited range of taxa to survive. Among the animal groups with the greatest diversity are insects. The purpose of this study was to determine the diversity of flying insects found in the oil palm plantation area of Wonosari District, Boalemo Regency. The method used in this research is exploration with three observation stations. Station I is adjacent to residential areas, station II is in the oil palm plantation area and station III is adjacent to residents' plantations. Sampling using the trap trap technique using the sweeping net method (insect net) which is commonly used for collecting flying insects. Sample identification in the Biology laboratory, Faculty of Mathematics and Natural Sciences, Gorontalo State University. The data obtained were analyzed descriptively. The results in this study obtained 12 species included in 5 orders and 8 families, namely: Family Nymphalidae (Faunis phaon pan, Amathusia phidippus, Melanitis leda). Pieridae family (Leptosia nina), Hesperiidae family (Platylesches robustus). Family Vespidae (Polistes fuscatus), Family Pyrgomorphidae (Atractomorpha crenulata), Family Acrididae (Trimerotropis pallidipennis, Oxya japonica, Chorthippus albomarginatus), Family Cerambycidae (Glenea albolineata) and Family Libellulidae (Neurothemis terminata) with a total of 24 individuals. Of all the flying insects found, the Diversity Index was 2.362, which indicates that diversity is classified as moderate.